Religion, Patriotism and War Experience in Digitized Wartime Letters in Finland, 1939–44. (July 2022) - Taskinen, Ilari; Turunen, Risto; Uusitalo, Lauri; Kivimäki, Ville
This article examines religious and patriotic languages in digitized letters written by ordinary Finnish people in the Second World War. We combine qualitative and quantitative methods to analyse how religious and patriotic languages were used throughout the war years. Our findings show that the frequency of religious and patriotic vocabulary fluctuated widely during the war. Religious words were most notably connected to the intensity of the warfare, peaking during the periods of heated combat and dropping in the period of stationary warfare. Patriotic words were likewise common during the early periods of combat, but their use waned in the later war years. The analysis of words occurring in close proximity to the religious and patriotic words suggests that this was due to the different functions of the two languages. Religious parlance was essentially a vehicle of private emotional coping, while patriotic style gave a collective meaning to the sacrifices of the war. Religion and patriotism diverged during the war because the collective meaning of the war vanished but the need for emotional comfort persisted until its end.